2009
DOI: 10.1002/clc.20354
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Manifestation of Myocardial Infarction in Elderly Patients

Abstract: Our observations confirm the differences in the clinical picture of MI in the elderly as described previously. All patients of advanced age should be considered as having the highest risk of death and complications occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 25 publications
3
39
0
1
Order By: Relevance
“…9,10 This was consistent with STEMI patients without chest pain in our study. In our study, none of the women smoked and in Taiwan, only 5.23% of women are smokers.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…9,10 This was consistent with STEMI patients without chest pain in our study. In our study, none of the women smoked and in Taiwan, only 5.23% of women are smokers.…”
supporting
confidence: 90%
“…10 In underlying diseases in ACS patients, women and elderly patients had a significantly higher prevalence of DM, HTN, and CVA. [8][9][10] The differences in peripheral vascular disease, heart failure, and myocardial infarction had conflicts in different studies. In our study, women accounted for 45.5% of patients without chest pain in STEMI, and patients were 9 years older than patients without chest pain (74.3±10.0 vs. 65.0±12.6, p<0.001, Table 3).…”
Section: Discussionmentioning
confidence: 95%
“…The most important and somewhat novel aspects identified by the task force were the following: (1) treatment of dyslipidaemia should not be considered as an isolated process, but rather within the context of integrated prevention of CVD in an individual patient. The SCORE scale is recommended as a basic tool for calculating CV risk; (2) therapeutic objectives: strengthening of strict low-density lipoprotein cholesterol (LDL-C) targets for patients with very high, high, and intermediate risk levels (no longer as an optional criterion) [4][5][6][7]; (3) non-pharmacological therapies: the relevance of diet and exercise not just in the reduction of total risk, but also in the specific treatment of dyslipidaemias [4,8]; (4) lipid-lowering drugs: a logical emphasis on statins as an essential treatment for cardiovascular prevention, and scarce details on fibrates, niacin, and absorption inhibitors; (5) dyslipidaemia treatment in special clinical situations: the detailed description of targets and prescriptions in several situations and subgroups [4,9,10].…”
Section: Lipidology Update 2011mentioning
confidence: 99%
“…The clinical features of acute myocardial infarction in older patients differs compared to younger patients (2). The specificity of acute myocardial infarction symptoms declines with increased age and patients over 80 years old show similar symptoms (14).…”
mentioning
confidence: 99%
“…Importantly, these other studies that were discussed did not appear to adjust their analysis for the effects of gender. Goch et al (2009), showed a high prevalence of diabetes, hypertension, and a lower prevalence of smoking and dyslipidemia in older myocardial infraction patients (2). However, Scoenenberger et al (2011), identified that dyslipidemia and smoking are prevalent in younger myocardial infraction patients (43).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%